Negative selection on human genes underlying inborn errors depends on disease outcome and both the mode and mechanism of inheritance - Rapaport, Franck; Boisson, Bertrand; Gregor, Anne; Béziat, Vivien; Boisson-Dupuis, Stéphanie; Bustamante, Jacinta; Jouanguy, Emmanuelle; Puel, Anne; Rosain, Jérémie; Zhang, Qian; Zhang, Shen Ying; Gleeson, Joseph G.; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2021)
Genetic variants underlying life-threatening diseases, being unlikely to be transmitted to the next generation, are gradually and selectively eliminated from the population through negative selection. We study the determinants of this evolutionary process in human genes underlying monogenic diseases by comparing various negative selection scores and an integrative approach, CoNeS, at 366 loci underlying inborn errors of immunity (IEI). We find that genes underlying autosomal dominant (AD) or X-linked IEI have stronger negative selection scores than those underlying autosomal recessive (AR) IEI, whose scores are not different from those of genes not known to be disease causing. Nevertheless, genes underlying AR IEI that are lethal before reproductive maturity with complete penetrance have stronger negative selection scores than other genes underlying AR IEI. We also show that genes underlying AD IEI by loss of function have stronger negative selection scores than genes underlying AD IEI by gain of function, while genes underlying AD IEI by haploinsufficiency are under stronger negative selection than other genes underlying AD IEI. These results are replicated in 1,140 genes underlying inborn errors of neurodevelopment. Finally, we propose a supervised classifier, SCoNeS, which predicts better than state-of-the-art approaches whether a gene is more likely to underlie an AD or AR disease. The clinical outcomes of monogenic inborn errors, together with their mode and mechanisms of inheritance, determine the levels of negative selection at their corresponding loci. Integrating scores of negative selection may facilitate the prioritization of candidate genes and variants in patients suspected to carry an inborn error.
CRIS-Team Scopus Importer:2021-01-22
Keywords: Immunodeficiency | selection | evolution | genetics | method